IMPROVING INTUITION SKILLS WITH REALISTIC MATHEMATICS EDUCATION - Hirza, Bonita; Kusumah, Yaya S.; Darhim, Darhim; Zulkardi, Zulkardi (Journal on Mathematics Education, 2014)
The intention of the present study was to see the improvement of students’ intuitive skills. This improvement was seen by comparing the Realistic Mathematics Education (RME)-based instruction with the conventional mathematics instruction. The subject of this study was 164 fifth graders of elementary school in Palembang. The design of this study was a Pretest-Posttest Control Group Experiment. Data was analyzed with the help of SPSS. The result of this study showed that there was different improvement of students’ skills. The improvement was higher in the class using the RME-based instruction that in conventional mathematics class.Keywords: Realistic Mathematics Education (RME), Intuition DOI: http://dx.doi.org/10.22342/jme.5.1.1446.27-34